Inactivation of Salmonella on black peppercorns using an integrated ultraviolet-C and cold plasma intervention. (January 2021) - Bang, In Hee; In, Jiwon; Min, Sea C.
Abstract: A nonthermal process that applies ultraviolet (UV)–C and helium cold plasma (CP) simultaneously (UV-CP) has been investigated as an intervention technology to inactivate Salmonella on black peppercorns. The optimum CP treatment voltage and UV-CP treatment time for inactivating Salmonella on black peppercorns were predicted using a model equation as 9.7 kV and 22.1 min, respectively, which non-thermally inactivated Salmonella by 3.7 log CFU/g. UV-CP treatment yielded a stronger bactericidal activity than UV treatment alone, without inducing photoreactivation. In addition, UV-CP-induced reactive species were similar to those found in individual UV and CP treatments. Furthermore, UV-CP treatment caused a profound deformation of Salmonella morphology and a greater extent of DNA damage than UV or CP treatment did alone. UV-CP treatment did not alter the color or 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activity; however, it lowered the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity and piperine concentration in the peppercorns. The findings of this study demonstrate the potential application of UV-CP treatment for decontamination of black peppercorns. Highlights: UV-cold plasma (CP) treatment effectively inhibits Salmonella in black peppercorns. The polynomial model adequately predicts Salmonella inactivation by UV-CP UV-CP treatment does not induce photoreactivation of Salmonella in the peppercorns. UV-CP treatment disintegrates the cellular structure and damages Salmonella DNA. UV-CP treatment is non-thermal and does not alter the color of black peppercorns.